2021
DOI: 10.1016/j.toxrep.2021.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tannic acid-templated mesoporous silica nanoparticles on iron-induced oxidative stress and liver toxicity in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Tannic acid has the ability to form a complex with polyvalent cations like Cd 2+ , Co 2+ , Cr 3+ , Zn 2+ and Fe 2+ . [118][119][120][121] Kim et al developed tannic acid-Fe(III) complex deposition on the surface of MSNs to provide the pH-and glutathione-responsive nanocarrier. The results of in vitro release study revealed sustainable Cur release at pH 7.4, while a rapid Cur release was observed by lowering the pH to 6.0 or 4.5.…”
Section: Glutathione (Gsh)-responsive Cur-loaded Msnsmentioning
confidence: 99%
“…Tannic acid has the ability to form a complex with polyvalent cations like Cd 2+ , Co 2+ , Cr 3+ , Zn 2+ and Fe 2+ . [118][119][120][121] Kim et al developed tannic acid-Fe(III) complex deposition on the surface of MSNs to provide the pH-and glutathione-responsive nanocarrier. The results of in vitro release study revealed sustainable Cur release at pH 7.4, while a rapid Cur release was observed by lowering the pH to 6.0 or 4.5.…”
Section: Glutathione (Gsh)-responsive Cur-loaded Msnsmentioning
confidence: 99%